Pendampingan Guru Pos PAUD Tepadu dalam Pembuatan Media Pembelajaran Pada Anak - Destita Shari; Andini Hardiningrum; Berda Asmara; Machmudah Machmudah; Mujad Didien Afandi (Indonesia Berdaya, 2023)
The learning process in schools requires the role of the teacher indirecting, guiding andi providing knowledge to students. In the learing process in early childhood, it is necessary to plan learning and learning media in learing activities. To optimize these activities, educators are expected to optimize the abilities and knowledge gained through mentoring activities in making learning media to be more creative and innovative. The location of the implementation of community service activities at the Pos Paud Terpadu Sekar Wangi Surabaya. The method implemented in assisting the manufacture of learning media is problem identification, discussion, evaluation. The result of community service activities is that the implementation of assistance in making learning media for Pos PAUD Terpadu is very effective for educators. The achievement of the implementation of mentoring activities consists of the suitability of learning planning, learning media adapted to the activity design. Implementation educators are required to design learning activities and learning media used, communicate in the process of learning activities. Abstrak: Proses pembelajaran di sekolah diperlukan peran guru dalam mengarah, membimbing dan memberikan pengetahuan untuk peserta didik.  Pada proses pembelajaran pada anak usia dini diperlukan perencanaan pembelajaran dan media pembelajaran pada kegiatan belajar. Untuk mengoptimalkan kegiatan tersebut pendidik diharapkan dapat mengoptimalkan kemampuan dan pengetahuan yang di dapatkan melalui kegiatan pendampingan pembuatan media pembelajaran agar lebih kreatif dan inovatif. Lokasi pelaksanaan kegiatan pengabdian kepada masyarakat di Pos Paud Terpadu, Sekar Wangi  Surabaya. Metode  yang dilaksanakan pada pendampingan pembuatan media pembelajaran adalah identifikasi permasalahan, diskusi, evaluasi. Hasil kegiatan pengabdian kepada masyarakat adalah pelaksanaan pendampingan pembuatan media pembelajaran untuk pendidik Pos PAUD Terpadu sangat efektif untuk pendidik. Ketercapaian pelaksanaan kegiatan pendampingan terdiri dari kesesuaian perencanaan pembelajaran, media pembelajaran yang disesuaikan dengan rancangan kegiatan, Implementasi pendidik diwajibkan untuk merancang kegiatan pembelajaran dan media pembelajaran yang digunakan, menyampaikan dalam proses kegitan pembelajaran.